A physiological and proteomic study of poplar leaves during ozone exposure combined with mild drought. Issue 10 (3rd June 2013) - Bohler, Sacha; Sergeant, Kjell; Jolivet, Yves; Hoffmann, Lucien; Hausman, Jean‐Francois; Dizengremel, Pierre; Renaut, Jenny
Abstract : The occurrence of high‐ozone concentrations during drought episodes is common considering that they are partially caused by the same meteorological phenomena. It was suggested that mild drought could protect plants against ozone‐induced damage by causing the closure of stomata and preventing the entry of ozone into the leaves. The present experiment attempts to create an overview of the changes in cellular processes in response to ozone, mild drought and a combined treatment based on the use of 2D‐DiGE to compare the involved proteins, and a number of supporting analyses. Morphological symptoms were worst in the combined treatment, indicating a severe stress, but fewer proteins were differentially abundant in the combined treatment than for ozone alone. Stomatal conductance was slightly lowered in the combined treatment. Shifts in carbon metabolism indicated that the metabolism changed to accommodate for protective measures and changes in the abundance of proteins involved in redox protection indicated the presence of an oxidative stress. This study allowed identifying a set of proteins that changed similarly during ozone and drought stress, indicative of crosstalk in the molecular response of plants exposed to these stresses. The abundance of other key proteins changed only when the plants are exposed to specific conditions. Together this indicates the coexistence of generalized and specialized responses to different conditions.